The cheese burglar: mini mystery 6 - STILTON, GERONIMO; GERONIMO STILTON (New York Scholastic, Inc, 2008)
Geronimo is wrongly accused of stealing prized antique cheese rinds at the Mouse Island Cheese Exhibition.
Keywords: the main suspect in a crime; the importance of honesty, empathy, and integrity